A highly efficient cathode based on modified graphite felt for aniline degradation by electro-Fenton. (November 2019) - Ou, Bin; Wang, Jixiao; Wu, Ying; Zhao, Song; Wang, Zhi
Abstract: The graphite felt (GF) was modified through the concentrated sulfuric acid, potassium permanganate and ammonia activation with the aim of improving the specific surface area, hydrophilicity and the electrocatalytic activity for the electrogeneration of hydrogen peroxide and its application in the electro-Fenton (EF). The modified graphite felt (M-GF) was characterized by contact angle, scanning electron microscope, X-ray photoelectron spectroscopy, Raman spectrum, cyclic voltammetry and electrochemical impedance spectroscopy. The surface physic-chemical characteristics and morphology of the M-GF were considerably changed after the modification. The current efficiency for H2 O2 generation was explored at an optimized current density of 10 mA cm −2 and the value of H2 O2 generation for the M-GF was 478.6 mg L −1, while the GF was 276.5 mg L −1 after 360 min of electrolysis. Finally, the M-GF was used for the mineralization of aniline (100 mg L −1 ), reaching a mineralization percentage of 97% with EF process. The M-GF demonstrated good stability as the aniline mineralization percentage was above 90% after 10 cycles' degradation, indicating that the M-GF is a promising cathode material for improving the degradation and mineralization of others organic pollutants by the EF process. Highlights: Nitrogen and sulfur doped graphite felt was prepared. The M-GF increased the total mineralization of aniline by the EF process. Aniline mineralization ratio of M-GF was decreased by 6.7% after 10 cycles of use.